Maqāṣid al-Sharī’ah and Waqf: Their Effect on Waqf Law and Economy - Mohammad, Mohammad Tahir Sabit Haji (Intellectual discourse, 2018)
: Often researchers mention the purposes of waqf for which a donation is made for a cause or a group of beneficiaries, such as building mosques, creating graveyards, schools, and feeding the hungry, etc. Recently Muslim thinkers have linked the Five Sharia Objectives to the waqf, which are helpful and enlightening. Other scholars have extended horizons further by introducing some fundamental and general objectives of waqf that may affect various aspects of it, including law and regulation, governance, socioeconomic goals of the Ummah and da’wah Islāmiyah. These works need consolidation and further review, as offered in this paper.